A Comparative Study of Diesel Oil and Soybean Oil as Oil-Based Drilling Mud. (11th February 2015) - Agwu, Okorie E.; Okon, Anietie N.; Udoh, Francis D.
Abstract : Oil-based mud (OBM) was formulated with soybean oil extracted from soybean using the Soxhlet extraction method. The formulated soybean mud properties were compared with diesel oil mud properties. The compared properties were rheological properties, yield point and gel strength, and mud density and filtration loss properties, fluid loss and filter cake. The results obtained show that the soybean oil mud exhibited Bingham plastic rheological model with applicable (low) yield point and gel strength when compared with the diesel oil mud. The mud density measurement showed that soybean OBM was slightly higher than diesel OBM with mud density values of 8.10 lb/gal and 7.98 lb/gal, respectively, at barite content of 10 g. Additionally, the filtration loss test results showed that soybean mud fluid loss volumes, water and oil, were 13 mL and 10 mL, respectively, compared to diesel oil mud volume of 15 mL and 12 mL. Furthermore, the filtration loss test indicated that the soybean oil mud with filter cake thickness of 2 mm had a cake characteristic of thin and soft while the diesel oil mud resulted in filter cake thickness of 2.5 mm with cake characteristic of firm and rubbery. In comparison with previous published works in the literature, the soybean oil mud exhibits superior rheological and filtration property over other vegetable oil-based muds. Therefore, the formulated soybean oil mud exhibited good drilling mud properties that would compare favourably with those of diesel oil muds. Its filter cake characteristic of thin and soft is desirable and significant to avert stuck pipe during drilling operations, meaning that an oil-based drilling mud could be formulated from soybean oil.